Analisis Kebijakan Rekrutmen PTPS dalam Mewujudkan Prinsip Good Governance pada Pelaksanaan Pemilu - Ning Mukti Indrayani; Prasojo Ashar Nur Darmawan; Titis Srimurni (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2025)
The purpose of this study is to analyze the implementation of the recruitment policy for Polling Station Supervisors (PTPS) in Tempeh District and to assess the extent to which the principles of Good Governance are applied in the process. The background of this research stems from the importance of conducting elections that are transparent, accountable, and integrity-driven, in which the recruitment of supervisors serves as one of the determining factors for successful election oversight. This study employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving relevant parties, such as the District Election Supervisory Committee, PTPS candidates and members, as well as the local community. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the PTPS recruitment policy in Tempeh District has generally been conducted in accordance with applicable regulations. However, several challenges remain, including limited time, suboptimal dissemination of information, and difficulties in maintaining the objectivity of the selection process. The application of Good Governance principles is reflected in the efforts to ensure transparency and accountability, although the aspects of participation and effectiveness still require improvement. The main supporting factors for policy implementation include strong coordination among election organizers and community support, while the inhibiting factors consist of limited human resources and technical constraints in the field. Overall, this study underscores the importance of applying Good Governance principles at every stage of the PTPS recruitment process in order to realize an election governance system that is honest, fair, and trustworthy.